“PET REDES SAUDI”: FAILURES OF EXAMINATION OTOACOUSTIC EMISSIONS IN NEWBORN HEARING SCREENING OF A MATERNITY – MACAÉ/RJ. (Fiep Bulletin - online, 2016)
Early identification of hearing impairment, which may adversely affect the quality of human life, is performed from the newborn hearing screening (NHS), if possible, even on maternity. This study aimed to describe the incidence of faults in neonatal hearing screening of newborns in the maternity ward of the Municipal Public Hospital in Macaé (HPMM). We conducted a descriptive study, of secondary basis in maternity of Municipal Public Hospital in Macaé (HPMM), between January and October 2013. Results of transient evoked otoacoustic emissions (TEOE) were collected from medical records of newborns Rooming and were in the Neonatal Intensive Care Unit. Data were analyzed from the relative distribution, using Microsoft Excel 2010 software. The study analysed 1321 TEOE test were performed in newborns in maternity HPMM between January and October 2013. In January, the 120 tests, were detected 5% of failures. In March (n=135), 8% of faults were found. In April (n=144), 16% were detected faults. In May (n=160), 7.5% detected faults. In June (n=156), 18% of faults were detected. In July (n=151), 12% were detected faults. In August (n=118), 11% were detected faults. In September (n=142), 9% of failures were observed. In October (n=169), 10% of detected faults. It is concluded that the percentage of failures in the examination of TEOE in neonates was high. It is necessary to conduct further studies to understand the factors related to these findings as well as knowing the reference and counter reference to possible cases of hearing loss.
Keywords: Hearing Test; Children's Health; Hearing Health.